Ammonium molybdate phosphate functionalized silicon dioxide impregnated in calcium alginate for highly efficient removal of 137Cs from aquatic bodies. Issue 98 (6th October 2016) - Saha, Sudeshna; Singhal, R. K.; Basu, H.; Pimple, M. V.
Abstract : Development of new hybrid material (SiO2 -AMP–Ca-Alg beads) for cesium uptake without disturbing the water quality parameters. Abstract : In this study, silica functionalized with ammonium molybdate phosphate (AMP) impregnated in calcium alginate (SiO2 -AMP–Cal-Alg) was developed for the highly efficient removal of radioactive cesium from aquatic media. During the synthesis, a compact protective interlayer of silica was deliberately constructed to stabilize the AMP. The optimum composition of the SiO2 -AMP–Cal-Alg beads was evaluated as 6% AMP modified SiO2 loaded into 4% calcium alginate. Because of high ion exchange capacity of the AMP functional layer, the SiO2 -AMP–Cal-Alg has high removal efficiency (>91%) of radioactive cesium from 137 Cs spiked solutions (3000–35 000 Bq L −1 ) and contaminated seawater. Batch experiments revealed that adsorption equilibrium was rapidly achieved within 30 min and the maximum sorption capacity was up to 37.52 mg g −1 . Kinetic models and adsorption isotherm equations (Langmuir/Freundlich) were used to fit the experiment data for describing the sorption process. These SiO2 -AMP–Cal-Alg beads are proposed to hold great promise for the clean-up of radiocesium contaminated water around nuclear facilities after nuclear accidents.